2018
DOI: 10.1007/s10047-018-1022-9
|View full text |Cite
|
Sign up to set email alerts
|

Simple method to make a supersaturated oxygen fluid

Abstract: Intravenous oxygenation has demonstrated significant increase in partial pressure of oxygen (PO) in animal models. A highly dissolved oxygen solution might be able to provide a sufficient level of oxygen delivery to the tissues and organs in patients with hypoxia. However, conventional fluid oxygenation methods have required the use of original devices. If simpler oxygenation of a solution is possible, it will be a useful strategy for application in clinical practice. We simply developed its administration by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…We demonstrated that the pO 2 and DO 2 in the blood increase significantly using a saturated oxygen solution. Our findings supported the results of the previous studies [7,10,11]. Critically ill patients with hypoxia need blood oxygenation.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We demonstrated that the pO 2 and DO 2 in the blood increase significantly using a saturated oxygen solution. Our findings supported the results of the previous studies [7,10,11]. Critically ill patients with hypoxia need blood oxygenation.…”
Section: Discussionsupporting
confidence: 93%
“…Preparing saturated oxygen solutions has been considered difficult because of the need of original devices [10][11][12]. However, we developed a saturated oxygen solution using a simple method [7]. This method resulted in the increase in the pO 2 more than 500 mmHg.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The oxygen tension of the liquid is expected to approach 150 mmHg when the diffusion of oxygen in contact with air reaches equilibrium by Henry’s and Fick’s law [(atmospheric pressure - water vapor pressure at 37°C)×F I O 2 : (760-47)×0.21≒150]. The PaO 2 of a small amount of bovine blood mixed with a saline solution equilibrated under air has been reported to be 165.8 ± 1.2 mmHg [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The data presented here shows production of a solution that contains NO with reference to an article [1]. The supplemental fluid (Sublood BSG, Fuso) was used as the test solution.…”
Section: Data Descriptionmentioning
confidence: 99%